Pre-scaling up evaluation of banana technology under irrigation conditions in Abergelle District, Wag-himra Zone, Ethiopia - Wubet, A.; Assefa, N.; Mihretu, A.; Ayen, K. (International Journal of Horticultural Science, 2022)
The study was conducted to compare the improved banana technology against the local production technique to enhance demand-driven banana technology up-scaling and diffusion. Data were collected at the field and farmers’ levels. Descriptive and inferential statistics, cost-benefit analysis and matrix ranking were employed for analysis. The result revealed that the average yield (38.40 ton ha-1) of improved banana technology had a significant yield advantage (47.24%) over the local practice (p<0.05). Despite the higher cost of production, its net return was by far higher than the local practice. The benefit-cost ratio also displays that 9.49 Ethiopian Birr (ETB) profit per 1.00 ETB investment in an improved technology package. The overall farmers’ perceptions were laid under strongly agree and agree categories, and 95% of them believed that the improved banana technology was appropriate for their area and hence accepted with full confidence. The respective organizations working on rural livelihood improvement are therefore advised to up-scale the improved technology for the wider community based on the irrigation potential.